The Lusitania Province as a center of diversification: the phylogeny of the genus Microlipophrys (Pisces: Blenniidae) - Martínez-Levy, Gabriela A. (2018)
The Lusitania Province has been considered a transition zone between the Atlantic northern cold waters and Tropical warm waters. Tropical species have expanded their ranges during warm periods and either retreated during cold periods or survived in local refuges. Successive waves of dispersion into this Province could have favored diversification through geographic isolation. Taxa that remained in this large Province may also have diversified in loco. We analyzed molecular markers of the genus Microlipophrys (family Blenniidae) that confirm the validity of this genus and of the seven recognized species. Microlipophrys and its sister clade apparently originated within Lusitania and dispersed into the tropics at a later stage. (C) 2010 Elsevier Inc. All rights reserved.